Evaluation of the Short Term Outcome of Unilateral Urethral Mobilization Compared to Circumferential Urethral Mobilization for the Management of Bulbar Urethral Stricture (Bangladesh Journal of Urology, 2020)
Objective: To evaluate and compare the outcome of buccal mucosal graft urethroplasty of unilateral and circumferential urethral mobilization for the management of bulbar urethral stricture.Methods: Seventy patients having bulbar urethral strictures admitted in the Department of Urology, Dhaka Medical College Hospital, Dhaka between January 2010 to December 2011. Patients were divided into two groups. Group-I, underwent unilateral urethral mobilization, and Group-II, underwent circumferential urethral mobilization for buccal mucosa graft urethroplasty. All patients were followed up at least six months. The statistics used to analyze the data were descriptive statistics, and p value